Anosmia dan ageusia sebagai faktor prognosis baik pada pasien COVID-19 rawat inap di RSUP Sanglah Denpasar - Senja Decy Ningrum; Ida Bagus Ngurah Rai; I Gede Ketut Sajinadiyasa; Anak Agung Raka Sudewi; Ida Ayu Jasminarti Dwi Kusumawardani; Ni Wayan Candrawati; Ni Luh Putu Eka Arisanti (Intisari Sains Medis, 2022)
Background: Anosmia and ageusia are early symptoms that are widely reported in COVID 19 patients and are associated with low rates of intensive care and mortality, so the hypothesis arises that anosmia and ageusia can be good prognostic factors in COVID-19 patients. This study aims to examine anosmia and ageusia as prognostic factors in COVID-19 patients. Methods: This study is an observational analytic study with a retrospective cohort design conducted at Sanglah General Hospital Denpasar from January to June 2022. Results: obtained a total of 1048 subjects with 344 subjects experiencing anosmia, 210 subjects experiencing ageusia, and 474 subjects experiencing a combination of anosmia and ageusia. Variable symptoms of anosmia and ageusia were statistically significant predictors for the recovery of COVID-19 patients (p<0.05). The cure rate in the group of patients with symptoms of anosmia was 1.8 times (RR = 1.783, 95% CI = 1.667-1.908) and the group of patients with symptoms of ageusia experienced 1.6 times higher recovery (RR = 1.564, 95% CI = 1.478 -1,655). After adjusting for other variables as confounders, the combination of symptoms of anosmia and ageusia in patients was a significant predictor of recovery for COVID-19 patients by 1.5 times compared to patients who did not experience the combination of symptoms of anosmia and ageusia (ARR = 1.523, 95% CI = 1.245- 1.864, p<0.05). Conclusion: Anosmia, ageusia and the combination of both, indicate protective factors against possible mortality and indicate a good prognosis in COVID-19 patients.   Latar belakang: Anosmia dan ageusia merupakan gejala awal yang banyak dilaporkan pada pasien COVID-19 serta dikaitkan dengan tingkat rawat intensif dan mortalitas yang rendah sehingga muncul hipotesis bahwa anosmia dan ageusia dapat menjadi faktor prognosis yang baik pada pasien COVID-19. Penelitian ini bertujuan untuk meneliti anosmia dan ageusia sebagai faktor prognosis pada pasien COVID- 19. Metode: Penelitian ini merupakan studi analitik observasional dengan rancangan kohort retrospektif yang dilakukan di RSUP Sanglah Denpasar pada bulan Januari    hingga Juni 2022. Hasil: Didapatkan total 1048 subjek dengan 344 subjek mengalami anosmia, 210 subjek mengalami ageusia, serta 474 subjek mengalami kombinasi anosmia dan ageusia. Variabel gejala anosmia maupun ageusia secara statistik merupakan prediktor signifikan untuk kesembuhan pasien COVID-19 (p<0,05). Tingkat kesembuhan pada kelompok pasien bergejala anosmia mencapai 1,8 kali (RR = 1,783, IK 95% = 1,667-1,908) lebih tinggi dan kelompok pasien bergejala  ageusia mengalami kesembuhan 1,6 kali lebih tinggi (RR = 1,564, IK 95% = 1,478-1,655). Setelah disesuaikan dengan variabel lain sebagai perancu, kombinasi gejala anosmia dan ageusia pada pasien menjadi prediktor kesembuhan pasien COVID-19 secara signifikan sebesar 1,5 kali lipat dibandingkan pasien yang tidak mengalami kombinasi gejala anosmia dan ageusia (ARR = 1,523, IK95% = 1,245-1,864, p<0,05). Simpulan: Anosmia, ageusia, dan kombinasi keduanya menunjukkan adanya faktor  protektif terhadap kemungkinan mortalitas serta menandakan adanya prognosis yang baik pada pasien COVID-19